2017
DOI: 10.1016/j.jaci.2016.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus immunoprophylaxis in high-risk infants and development of childhood asthma

Abstract: Background Respiratory syncytial virus (RSV) lower respiratory tract infection is implicated in asthma development. RSV immunoprophylaxis during infancy is efficacious in preventing RSV hospitalizations and has been associated with decreased wheezing in the first years of life. Objective We investigated whether greater adherence to immunoprophylaxis in infants at high-risk for severe RSV would be associated with decreased childhood asthma. Methods We conducted a retrospective cohort investigation including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…59 Two studies of RSV immunoprophylaxis with palivizumab in preterm or high-risk infants demonstrated that prevention of more severe RSV-induced illness decreased recurrent wheezing but not atopic asthma. 60,61…”
Section: Rsvmentioning
confidence: 99%
“…59 Two studies of RSV immunoprophylaxis with palivizumab in preterm or high-risk infants demonstrated that prevention of more severe RSV-induced illness decreased recurrent wheezing but not atopic asthma. 60,61…”
Section: Rsvmentioning
confidence: 99%
“…Another RSV antibody, motavizumab, administered to a high-risk group in the first year of life reduced the risk of hospital admissions for wheezing by 87% but did not lead to a reduction in medically treated wheezing between 1 and 3 years of age. 49 Taken together, these studies indicate that monoclonal antibody therapy directed against RSV in preterm infants can reduce bronchiolitis and recurrent wheezing. Whether similar results would be seen in full-term infants remains to be demonstrated.…”
Section: Prevention and Treatmentmentioning
confidence: 83%
“…Two studies (Carroll et al and Simoes et al) [38] [41] were graded as being of very low quality with serious risk of bias. Carrol et al was deemed to show considerable risk of bias given infants most at risk of both RSV and development of recurrent wheeze, were more likely to have increased uptake and compliance with monoclonal antibody prophylaxis, potentially skewing results.…”
Section: Sub-group Analysesmentioning
confidence: 99%